Zwei Kapitel aus der Frühgeschichte der Münchener Rückversicherung [Two Chapters on early history of the Munich Reinsurance Company: The Foundation/ The San Francisco Earthquake] - Reinhard Spree (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
– The Munich Re was founded in 1880 and is from the very start till this day one of the leading insurance companies in the world. Despite its long and successfull existance the company's history has not been reported yet in a way that fulfilled scientific criteria. This paper can be seen as a first step in this direction. Following a biographical approach the focus will be set on the co-founder and first general director, Carl Thieme, who chaired the company for several decades. The first chapter will outline the foundation of the Munich Re while the second chapter will give an examination of the way the Munich Re dealt with the challenge of the San Francisco earthquake of 1906.
urn:nbn:de:bvb:19-epub-11336-5
Keywords: E22; E51; F23; F53; G22; N21; N23; 330; insurance; reinsurance; institutions; globalization; global players; economic success; earthquake; San Francisco; Munich; Rückversicherung; Unternehmensgründung; Unternehmensgeschichte; Multinationales Unternehmen; Erfolgsfaktor; Deutschland (bis 1945); Erdbeben; Versicherungsschaden; San Francisco (Calif.)